EVALUACIÓN DEL DESEMPEÑO DE LOS EXPOSITORES EN FERIAS INTERNACIONALES - Angles Sánchez, Enrique (2017)
International fairs are an international marketing tool generally used by exporting companies. Despite its advantages, in the case of the Peruvian exporting companies a limited participation as exhibitors is evidenced, and the few that participate do not come to evaluate the performance of their participation. The present study is aimed at proving if the exhibiting companies evaluate their fair performance mainly through the sales obtained, as the existing literature indicates. For this, we worked a fair performance model from the sales. For the quantitative empirical analysis, a specific survey was applied to Peruvian exhibitors of the two most important trade fairs in the clothing, fashion and handicraft sectors. The results showed that the sales, from their participation in the fair, have a positive and significant correlation with the evaluation of their fair performance.